Breast tissue and breast cancer risk in abnormal secernation - G. Kh. Khanafiev (Опухоли женской репродуктивной системы)
From 122 of women with aseptic discharge from breast milk glands in 42.6 % of the cases in history was celebrated mastitis or postpartum lactostasis (25.4 %). Study the contents of the bile ducts, the state of periductale tissue of mammary glands of these women showed that a high titer of bacterial invasion was typical for women in the age of 35–55 years as among parous (10.7 %), and in nulliparous (8.2 %). The proliferating epithelium in the ducts is more marked in women who have had an abortion (4.9 %) and parous women of reproductive age (4.1 %). For сецернирующих of mammary glands is more characteristic of differentiation on the grounds of proliferation and autoimmunisacion. Cistic-advanced ducts, as a source of excessive hormone concentrations, leading to displastic processes of the walls of the cystic formations and periductale tissue, is an indication for the beginning of the immediate treatment of the patient.